Diagnostic precision of retinal nerve fiber layer and macular thickness asymmetry parameters for identifying early primary open-angle glaucoma. - Sullivan-Mee, Michael; Ruegg, Claudia C; Pensyl, Denise; Halverson, Kathy; Qualls, Clifford (American Journal of Ophthalmology, 2013)
Purpose: To evaluate the diagnostic capabilities of intereye and intraeye differences in retinal nerve fiber layer (RNFL) thickness and macular thickness for identifying early primary open-angle glaucoma (POAG).Design: Prospective, cross-sectional cohort study.Methods: All subjects were enrolled from an ongoing institutional glaucoma study. We used spectral-domain optical coherence tomography (Spectralis; Heidelberg Engineering) to obtain macular thickness (posterior pole asymmetry scan) and RNFL thickness (circumpapillary scan) in both eyes of 50 early POAG and 50 control subjects. Early POAG subjects had glaucomatous optic neuropathy with mild, reproducible visual field loss in at least 1 eye, and control subjects had normal intraocular pressures, visual fields, and optic nerves. We recorded total, superior, and inferior RNFL and macular thicknesses and then calculated intereye and intraeye differences (asymmetry parameters). Statistical evaluation included receiver operating characteristic and multivariate logistic regression analyses.Results: Intereye macular thickness asymmetry had the highest diagnostic sensitivity (88% at 80% specificity; 83% at 95% specificity), followed by total RNFL thickness (88% at 80% specificity; 75% at 95% specificity). Parameters with the largest areas under the receiver operating characteristic curves were: total RNFL thickness (0.937), intereye RNFL asymmetry (0.921), intereye macular thickness asymmetry (0.913), inferior RNFL thickness (0.905), superior RNFL thickness (0.887), intereye inferior macular thickness asymmetry (0.872), and intraeye macular thickness asymmetry (0.860). These 7 values were not significantly different. In multivariate logistic regression analyses, intraeye macular thickness asymmetry, intereye macular thickness asymmetry, intereye RNFL thickness asymmetry, and total RNFL thickness were related independently to early POAG.Conclusions: Structural asymmetry parameters performed well, identifying early POAG as well as RNFL thickness. Further study is indicated to validate these results.